2022
DOI: 10.1101/2022.07.07.22277297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide determinants of mortality and motor progression in Parkinson’s disease

Abstract: Background: There are 90 genetic risk variants for Parkinson's disease (PD) but currently only five nominated loci for PD progression. The biology of PD progression is likely to be of central importance in defining mechanisms that can be used to develop new treatments. Methods: We studied 6,766 PD patients, over 15,340 visits with a mean follow-up of between 4.2 and 15.7 years and carried out a genome wide survival study for time to motor progression, defined by reaching Hoehn and Yahr stage 3 or greater, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Our approach aims to compare progression across multiple diseases and comes at expenses of a tailored definition of progression for each disease. Nonetheless, disease-specific mortality has been widely used as a measure of progression (Hernesniemi, 2022; Jabbari et al, 2021; Tan et al, 2022; Wu et al, 2014). In practice, biobank-based studies of disease progression often need to converge to simple definitions to maximise sample size, and disease-specific mortality is an information typically available across biobanks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach aims to compare progression across multiple diseases and comes at expenses of a tailored definition of progression for each disease. Nonetheless, disease-specific mortality has been widely used as a measure of progression (Hernesniemi, 2022; Jabbari et al, 2021; Tan et al, 2022; Wu et al, 2014). In practice, biobank-based studies of disease progression often need to converge to simple definitions to maximise sample size, and disease-specific mortality is an information typically available across biobanks.…”
Section: Discussionmentioning
confidence: 99%
“…Among neurological conditions, GWAS have focused on disease survival as well as cognitive or motor decline. In one of the largest studies, researchers have identified three novel loci associated with Parkinson’s disease progression (Tan et al, 2022). A recent study on multiple sclerosis progression has identified a locus pointing to involvement of the central nervous system in disease outcome as opposed to the enrichment for immunological-related signals observed for disease susceptibility (Harroud et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“… Liu et al (2021) , in a study of 3,821 patients, identified three novel loci associated with cognitive progression in PD, in addition to confirming associations with GBA1 and APOE. Tan et al (2022) , in an analysis of 11 cohorts from Europe and the Americas, including the PPMI, Tracking Parkinson’s, and Oxford Discovery cohorts ( Lawton et al, 2022 ), identified six novel loci associated with PD motor progression or mortality, and found that the E326K GBA1 variant was associated with increased mortality. Martínez Carrasco et al (2023) , in a GWAS meta-analysis, identified an association between axial motor progression and expression of ACP6 that suggests mitochondrial lipid homeostasis plays a role in motor progression.…”
Section: Discussionmentioning
confidence: 99%